Waqf .. between the reasonableness of the meaning and the interest of the purpose?! A tour in a book: "Realizing the benefit of the Waqf" : by Dr. Abdullah bin Bayh (مجلة وقف في دراسات الاوقاف, 2026)
Introduction .. About the book's content:  Realizing the benefit of the Waqf is a book in which the scholar Abdullah bin Bayh presented insights and solid and rooted doctrinal solutions aimed at providing an opportunity for Waqfs, in order to enter the doors of goodness and the development of Muslim societies. This is a matter that the Sheikh believes that the first obstacle he faces, among other obstacles, is the jurisprudential view inherited in some schools, which makes the endowment static and not moving, standing and not walking, at a time when non-Islamic charitable institutions are diverse in the world, and these institutions competed in the provision of humanitarian services, using huge investments as a means to reap huge profits, which became a surplus property that meets the needs of charitable work without affecting the capital.  This obstacle has made many of the properties that were endowed for hundreds of years lose their value, and they do not generate any revenue for their destinations, as they were ruined without any replacements, lost without repairing, and the superintendents were fed up with them, so they did not spend them in the aspects of righteousness that this waqif did not mention at that time. These are issues and scientific issues that the Sheikh tries to discuss through the "base of benefits", and its undeniable impact.